Low cost and stable quinoxaline-based hole-transporting materials with a D–A–D molecular configuration for efficient perovskite solar cells. Issue 27 (22nd June 2018) - Zhang, Hao; Wu, Yongzhen; Zhang, Weiwei; Li, Erpeng; Shen, Chao; Jiang, Huiyun; Tian, He; Zhu, Wei-Hong
Abstract : Molecular hole-transporting materials containing a weak electron acceptor core can simultaneously improve the stability and photovoltaic performance of perovskite solar cells. Abstract : The use of expensive hole transporting materials (HTMs), such as spiro-OMeTAD, in perovskite solar cells (PSCs) is one of the critical bottlenecks to hinder their large-scale applications. Some low-cost alternatives have been developed by combining conjugated electron-rich cores with arylamine end-caps, usually in a donor–π spacer–donor (D–π–D) molecular configuration. However, incorporation of electron-rich cores can lead to undesirable up-shift in the HOMO energy level and low stability, and few of these new HTMs can outperform spiro-OMeTAD in terms of device efficiency. Given that electron-deficient units have shown many advantages in developing efficient and stable photovoltaic dyes and polymers, we herein present a couple of novel molecular quinoxaline-based HTMs (TQ1 andTQ2 ) with a donor–acceptor–donor (D–A–D) configuration, especially for rationally modulating the HOMO level, improving the stability and decreasing the cost. TheTQ2 -based PSCs exhibit a maximum efficiency of 19.62% (working area of 0.09 cm 2 ), unprecedentedly outperforming that of spiro-OMeTAD (18.54%) under the same conditions. In comparison, TQ1 based devices only showed moderate efficiencies (14.27%). The differences in hole extraction and transportation betweenTQ1 andTQ2 are explored by photoluminescence quenching, mobility and conductivity tests, and single crystal analysis. The scaling-up of theTQ2 based device to 1.02 cm 2 achieves a promising efficiency of 18.50%, indicative of high film uniformity and processing scalability. The significant cost advantage and excellent photovoltaic performance strongly indicate that the D–A–D featuredTQ2 has great potential for future practical applications.